Structural and acoustic properties of urbanized landscapes adversely affect bird communities in a tropical environment - Matthew, Dickson Anoibi; Osinubi, Samuel Temidayo; Ivande, Samuel Tertese; Iwajomo, Soladoye B.; Ottosson, Ulf (Frontiers in Ecology and Evolution, 2024)
IntroductionThe rural-urban gradient serves as a valuable context for investigating the impact of urbanization on biodiversity. While previous studies have demonstrated shifts in bird communities along this gradient, our understanding of the specific impacts of individual urban components such as man-made physical structures and anthropogenic noise along this gradient remains limited, and more so, in Afro-tropical environments.MethodEmploying the point count method, we recorded birds and also determined the levels of anthropogenic noise and physical structures, across fifteen sites along the rural-urban gradient on the Jos Plateau, Nigeria. We then investigated variations in bird communities along the urbanization gradient and assessed the influence of the two urban components -anthropogenic noise and physical structures, on bird populations.ResultsThere was a decline in bird abundance and species richness along the urbanization gradient. Similarly, species common to all the urbanization categories (species present at least at one point in rural, suburban, and urban) also exhibited a decrease in abundance. The suburban area showed a greater similarity in bird community composition to the urban area than the rural area. Notably, as the level of urban development increased, numerous bird species associated with undisturbed sites gradually vanished. Both anthropogenic noise and physical structures exhibited significant negative effects on bird abundance and species richness. Interestingly, we did not find evidence to suggest that the impact of anthropogenic noise was dependent on the level of physical structures. Anthropogenic noise had a significant negative relationship with bird abundance and species richness at all levels of physical structures.DiscussionWe provide evidence that bird abundance and species richness respond negatively to urbanization-related increase in anthropogenic noise and physical structures. That the impact of anthropogenic noise on birds was independent of physical structures suggests that birds in reserved areas, including urban green areas with fewer human activities may equally be affected by noise as are birds in human-dominated areas, if noise sources are near. Overall, our research underscores the detrimental consequences of anthropogenic habitat modification, particularly the alteration of structural and acoustic properties, and emphasizes the importance of preserving undisturbed habitats and implementing ecologically mindful urban planning strategies to safeguard bird communities in the Afro-tropics.